Multi-host infection and phylogenetically diverse lineages shape the recombination and gene pool dynamics of Staphylococcus aureus - Stephanie S. R. Souza; Joshua T. Smith; Spencer A. Bruce; Robert Gibson; Isabella W. Martin; Cheryl P. Andam (BMC Microbiology, 2023)
Abstract Background Staphylococcus aureus can infect and adapt to multiple host species. However, our understanding of the genetic and evolutionary drivers of its generalist lifestyle remains inadequate. This is particularly important when considering local populations of S. aureus, where close physical proximity between bacterial lineages and between host species may facilitate frequent and repeated interactions between them. Here, we aim to elucidate the genomic differences between human- and animal-derived S. aureus from 437 isolates sampled from disease cases in the northeast region of the United States. Results Multi-locus sequence typing revealed the existence of 75 previously recognized sequence types (ST). Our population genomic analyses revealed heterogeneity in the accessory genome content of three dominant S. aureus lineages (ST5, ST8, ST30). Genes related to antimicrobial resistance, virulence, and plasmid types were differentially distributed among isolates according to host (human versus non-human) and among the three major STs. Across the entire population, we identified a total of 1,912 recombination events that occurred in 765 genes. The frequency and impact of homologous recombination were comparable between human- and animal-derived isolates. Low-frequency STs were major donors of recombined DNA, regardless of the identity of their host. The most frequently recombined genes (clfB, aroA, sraP) function in host infection and virulence, which were also frequently shared between the rare lineages. Conclusions Taken together, these results show that frequent but variable patterns of recombination among co-circulating S. aureus lineages, including the low-frequency lineages, that traverse host barriers shape the structure of local gene pool and the reservoir of host-associated genetic variants. Our study provides important insights to the genetic and evolutionary factors that contribute to the ability of S. aureus to colonize and cause disease in multiple host species. Our study highlights the importance of continuous surveillance of S. aureus circulating in different ecological host niches and the need to systematically sample from them. These findings will inform development of effective measures to control S. aureus colonization, infection, and transmission across the One Health continuum.